Pembentukan Karakter Kewirausahaan melalui Manajemen Pesantren: Studi pada Pondok Pesantren di Indonesia - Salsabila Shafha Firabi Awwalia; Syaripudin Basyar; Junaidah (WISE Pendidikan Indonesia, 2026)
Entrepreneurship education in Islamic boarding schools is increasingly important for developing students who are not only religiously grounded but also independent, responsible, creative, and socially productive. This study aims to analyze how pesantren management contributes to the formation of students’ entrepreneurial character through entrepreneurship programs at an Indonesian Islamic boarding school. This research employed a qualitative case study design at Pondok Pesantren Darul Falah Bandar Lampung. Data were collected through observation, in-depth interviews, and documentation involving pesantren leaders, entrepreneurship program managers, teachers, and students. The data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. The findings show that entrepreneurial character formation was carried out through three interconnected management stages: planning, implementation, and evaluation. Planning was reflected in the formulation of entrepreneurship programs oriented toward students’ independence, responsibility, discipline, creativity, confidence, and risk-taking ability. Implementation was conducted through students’ direct involvement in pesantren business units, including a pesantren mart, café, fish pond, and garden. Evaluation was not limited to economic outcomes but also emphasized behavioral changes among students, particularly in responsibility, initiative, discipline, and self-reliance. This study concludes that pesantren-based entrepreneurship programs can function as both managerial and pedagogical instruments for character formation. The implication is that Islamic boarding schools need to manage entrepreneurship programs systematically and evaluate them based on students’ character development, not merely institutional economic productivity.